2019
DOI: 10.1111/jocs.14353
|View full text |Cite
|
Sign up to set email alerts
|

Neoangiogenesis connecting a left internal mammary artery proximal stump to an ischemic area of the heart after bypass occlusion

Abstract: Internal mammary arteries (IMAs), via angiogenesis/arteriogenesis, have great potential for developing collaterals. This generally occurs when ischemia involves the inferior limbs or heart. Although this phenomenon may be spontaneous, it seems to be promoted by iatrogenic or voluntary occlusion of the IMAs. We present a patient who underwent triple coronary artery bypass grafting with two saphenous vein grafts and a free-graft left IMA and suffered an acute myocardial infarction 6 weeks after surgery. Emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Meanwhile, angiogenic growth factors are applied to the internal mammary artery to enhance the development of new collateral branches, thereby promoting improved blood flow to the heart ( 54 ). Researches had shown that internal mammary artery occlusion can increase the blood supply of extracardiac ipsilateral coronary arteries, leading to reduced ischemia in dependent myocardial regions and alleviating angina symptoms in patients ( 55 , 56 ). Although internal mammary artery occlusion has not yet gained widespread recognition as a standard treatment method and requires further evidence-based research, it is considered a novel approach for refractory angina or a potential alternative to coronary sinus reducer therapy due to its significant anti-myocardial ischemia effect ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, angiogenic growth factors are applied to the internal mammary artery to enhance the development of new collateral branches, thereby promoting improved blood flow to the heart ( 54 ). Researches had shown that internal mammary artery occlusion can increase the blood supply of extracardiac ipsilateral coronary arteries, leading to reduced ischemia in dependent myocardial regions and alleviating angina symptoms in patients ( 55 , 56 ). Although internal mammary artery occlusion has not yet gained widespread recognition as a standard treatment method and requires further evidence-based research, it is considered a novel approach for refractory angina or a potential alternative to coronary sinus reducer therapy due to its significant anti-myocardial ischemia effect ( 57 ).…”
Section: Discussionmentioning
confidence: 99%